Studi Perbandingan Metoda WSD dan LRFD dalam Analisa Struktur Anjungan Lepas Pantai - Tawekal, Ricky L. (Department of Civil Engineering, Diponegoro University, 2004)
Up to this moment, most of structural design of offshore platforms are carried out by using traditional Allowable Stress Design (or Working Stress Design) specification adopted in American Petroleum Institute (API RP2A – WSD) Codes. In this method, loads and stresses are calculated based on linier elastic material and then compare them to the allowable loads and stresses. Recently, Load and Resistance Factor Design specification adopted in API RP2A – LRFD have been developed from the API RP2A – WSD using reliability based calibration. General industry practices recognise that older, existing offshore structures may not meet current design standards. However, many of these platforms that are in acceptable condition can be shown to be structutrally adequate using a risk based assesment criteria that considers platform use, location, and the consequences of failure. In this paper, a comparison study on WSD and LRFD methods in structural analysis of offshore platform is carried out by using a monopod offshore platform model. Structural analysis and unity check are performed by using SACS version 5.1 software. Keywords: working stress design, load and resistance factor design, offshore structures